2005
DOI: 10.1111/j.1365-2524.2005.00566.x
|View full text |Cite
|
Sign up to set email alerts
|

'I daresay I might find it embarrassing': general practitioners' perspectives on discussing sexual health issues with lesbian and gay patients

Abstract: The present paper explores general practitioners' (GPs') perspectives on the difficulties which they face when discussing sexual health issues with lesbian and gay patients in primary care consultations. It draws upon data obtained from a qualitative interview study with 22 GPs aged between 34 and 57 years who were practising in Sheffield, UK. Interviews were transcribed verbatim and the data were analysed thematically. The results indicate that (non-hetero)sexual orientation could form a barrier to talking ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
141
1
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(153 citation statements)
references
References 27 publications
9
141
1
2
Order By: Relevance
“…We found that training for medical, health and social care students at undergraduate and postgraduate levels about taking a proactive role during training consultations, not making assumptions about patients' sexual orientation and understanding what that may mean for their healthcare practice were all regarded as crucial factors for transforming healthcare for LGBT communities and is consistent with other recent research (Hinchliff, Gott, & Galena, 2005;Sequiera, Chakraborti, & Panunti, 2012). Particularly important was patient-centered communication in consultations, which has been associated with better health outcomes, owing to more recollection of information by the patient, treatment adherence and satisfaction with care (Hall, Roter, & Katz, 1988).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…We found that training for medical, health and social care students at undergraduate and postgraduate levels about taking a proactive role during training consultations, not making assumptions about patients' sexual orientation and understanding what that may mean for their healthcare practice were all regarded as crucial factors for transforming healthcare for LGBT communities and is consistent with other recent research (Hinchliff, Gott, & Galena, 2005;Sequiera, Chakraborti, & Panunti, 2012). Particularly important was patient-centered communication in consultations, which has been associated with better health outcomes, owing to more recollection of information by the patient, treatment adherence and satisfaction with care (Hall, Roter, & Katz, 1988).…”
Section: Discussionsupporting
confidence: 90%
“…Anti-discriminatory policy is vital for improving healthcare provision for LGBT people (Hinchliff et al, 2005). A number of accreditation documents have been developed to ensure non-discrimination, such as that produced by the Council of Social Work Education (CSWE Commission on Accreditation, 2008), which explicitly requires that continuous efforts to provide a learning context in which respect for all persons and understanding of diversity are practiced.…”
Section: Education Facilitating Good Healthcarementioning
confidence: 99%
See 1 more Smart Citation
“…Similarly to GPs in the UK, consultation timing and context were major challenges to discussing sexual health, practices and identity (Gott, Galena, Hinchliff, & Elford, 2004). Health discussions with LGBT patients focused almost exclusively on safe sex and STIs, consistent with other studies (Boehmer, 2002), which is unsurprising given that medical discourse on LGBT health issues in the Caribbean centers on HIV, and globally doctors lack information on LGBT patients' broader health needs (Bjorkman & Malterud, 2009;Hinchliff et al, 2004;Rutherford, McIntyre, Daley, & Ross, Sandfort (2010) suggested, legislating non-discrimination and decriminalizing homosexuality can improve health professionals' attitudes, behaviors, and training approaches. Whilst this will require wider activism and structural reform, the medical profession can advocate for such change and, in its absence, model sensitive, culturally competent care for LGBT patients.…”
Section: Discussionmentioning
confidence: 53%
“…Lesbian and bisexual women in numerous international studies continue to report the difficulties in accessing information on safe sexual practices, and feel that they cannot ''come out'' to their general practitioner or nurse because they have already assumed heterosexuality and/or fear being judged, discriminated against or having their confidentiality compromised (Bailey et al, 2003;Farquhar et al, 2001;Hunt & Fish, 2008;McNair, 2003;Platzer & James, 2000;Queiry, 2007;Steele, Tinmouth, & Lu, 2006;Stevens & Hall, 2001). These fears, it would appear, are not without some basis in that research with healthcare professionals has revealed assumptions of heterosexuality and uninformed attitudes regarding lesbian and gay lifestyles and sexual practices (Hinchliff, Gott, & Galena, 2005). Finally, and of particular importance here, young lesbian and bisexual women in Northern Ireland have reported that even when sexual health information and advice is offered to the lesbian, gay and bisexual community, it has tended to focus on male sexual orientation and the needs of young women are being overlooked (Lourdes, 2003).…”
Section: Lesbian Sexual Health: Common Myths and Their Consequencesmentioning
confidence: 99%